Peningkatan Kerjasama Anak Usia 5-6 Tahun Melalui Kegiatan Cooking Class - Aprida, Siti Nurul; Kurnia, Lita; Nurlela, Siti (LPPM STAI La Tansa Mashiro, 2024)
Activities together or in groups to achieve mutually agreed goals so that children's cooperative skills are born through good interaction. Cooking class is one of the concrete activities that can stimulate early childhood cooperation. The method used in this study is classroom action research of the PTK participant type with 2 cycles. Using PTK steps preaction, planning, action, observation, reflection. Using primary and secondary data sources. Data collection techniques observation, documentation and interviews. Qualitative descriptive data analysis techniques with percentages with stages of data reduction, data presentation and conclusion (verification). The results of the study showed an increase in cooperation between children aged 5-6 years at KB Subulussalam, Cibeber District after carrying out cooking class activities cycle I action 1 developed an average class of 30% and action 2 developed 40%. Cycle II action 1 developed the average class is still 40% action 2 developed the average class 60%, meaning the average class development at the end of the cycle was 42.5% of all subjects studied. The level of child improvement at the end of the cycle was 9 children (60%) Developing According to Expectations and 6 children (40%) Developing Very Well. Based on the results of the level of improvement obtained from this study, the cooking class activity can be a learning activity to improve cooperation of children aged 5-6 years at KB Subulussalam, Cibeber District, even though it has not reached the criteria of Developing Very Well. Keywords: Cooperation, Age 5-6 Years, Cooking Class Keywords: Cooperation, Age 5-6 Years, Cooking Class